Owner-occupied housing as an investment, regional house price cycles and residential sorting - Markus Haavio; Heikki Kauppi (Bank of Finland, 2011)
We develop a dynamic multi-region model, with fluctuating regional house prices, where an owner-occupied households location choice depends on its current wealth and its current type and involves both consumption and investment considerations. The relative strength of the consumption motive and the investment motive in the location choice determines the equilibrium pattern of residential sorting, with a strong investment (consumption) motive implying sorting according to the type (wealth). The model predicts a negative relation between the size of house price fluctuations and the degree of residential sorting in the type dimension. Also, movers should be more sorted than stayers in the type dimension. These predictions are consistent with evidence from US metropolitan areas when income, education and age are used as proxies for household type.
URN:NBN:fi:bof-20140807516
Keywords: D52; G11; R13; R21; R23; 330; Residential sorting; House prices; Consumption motive; Investment motive; Incomplete markets; Household mobility